Gender influence on participation in cassava value chains in smallholder farming sectors: evidence from Kigoma region, Tanzania - Masamha, Blessing; Uzokwe, Veronica N.E.; Ntagwabira, F.E.; Gabagambi, D.; Mamiro, P. (Cambridge University Press, 2019)
When the agricultural value chain involves profit making, it results in changes in the production and distribution relationships among men and women in terms of access to and control of markets, resources and benefits emanating from product value chain participation. This affects not only individual incomes but also gender equality. This study examined gender relationships in the cassava value chain in the Kigoma region of Tanzania. The aim was to assess gender participation in the cassava value chain. Multi-stage sampling was used to select the respondents in four districts. A structured questionnaire was administered to 384 randomly selected household heads. A chi-square test was used to test for significant relationships among the variables. Results indicated that gender was significantly related to socio-economic characteristics. About 34% of the women participating in the cassava value chain were young, some below 17 years of age. There were significant relationships between gender and access to resources (land, extension services and markets), control over resources (land, house and household assets) and benefits (revenue) generated from cassava value chains. Overall, there was gender disparity in participation along the cassava value chain. These results suggest that any intervention in the cassava value chain should consider gender relations to benefit men and women and alleviate household poverty.